2018
DOI: 10.1016/j.scitotenv.2018.04.130
|View full text |Cite
|
Sign up to set email alerts
|

Future irrigation expansion outweigh groundwater recharge gains from climate change in semi-arid India

Abstract: Simultaneous effects of future climate and irrigation intensification on surface and groundwater systems are not well understood. Efforts are needed to understand the future groundwater availability and associated surface flows under business-as-usual management to formulate policy changes to improve water sustainability. We combine measurements with integrated modeling (MIKE SHE/MIKE11) to evaluate the effects of future climate (2040-2069), with and without irrigation expansion, on water levels and flows in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Another set of terms refers to the policy process: policy-making, policy change, policy decision, policy reform, and policy process. Numerous scholars use the terms policymaking or policy change while highlighting the evidentiary value of their study for policy design [174][175][176]. For instance, Khosla, Dukkipati [177] propose multi-criteria decision analysis as a procedural tool for analytically rigorous, participative, and transparent policymaking.…”
Section: Policy Measure 49mentioning
confidence: 99%
“…Another set of terms refers to the policy process: policy-making, policy change, policy decision, policy reform, and policy process. Numerous scholars use the terms policymaking or policy change while highlighting the evidentiary value of their study for policy design [174][175][176]. For instance, Khosla, Dukkipati [177] propose multi-criteria decision analysis as a procedural tool for analytically rigorous, participative, and transparent policymaking.…”
Section: Policy Measure 49mentioning
confidence: 99%
“…The second objective of the paper is to develop a hydro-economic methodology to scientifically evaluate the viability of a representative lift irrigation scheme based on IWRM's framework of efficiency, equity ecological sustainability, and resource user's participation [8]. Past studies on minor irrigation projects have employed the conventional benefit-cost analysis (BCA) tool to evaluate economic viability and equity considerations of alternative water allocation measures under a variety of climate-related uncertainty [36][37][38][39]. BCA tool has also been widely used in other fields of investment decisions, for instance, renewable energy resource projects [40][41][42] and transportation projects [43,44].…”
Section: The Context Of This Studymentioning
confidence: 99%
“…This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/). ), Ashimane(44), Bommanalli(43), Bugadimane(41), Nagarakura(39), Kibbali(36), Golikoppa(35), Dalavaayi(35), Keshinamane(35), Halige (34), Keresara(33), Konkana(33), Manthaguli (30), Chowdi-2nd (29), Chowdi-1st (29), Kadave-1st (28), Beerala(27), Nidagod(27), Hakkimane-1st(27), Shindigere(26)Earth and Environment Department, Florida International University, MM Campus, Miami, FL 33199, USA; nchar042@fiu.edu 2 College of Fisheries, Mangalore 575002, India; rcbhat@gmail.com 3 Private Farmer, Bhairumbe, Sirsi 581405, Karnataka, India; krishnamhegde@gmail.com…”
mentioning
confidence: 99%
“…Mekonnen and Hoekstra (2016) reported that globally about 4 billion people live under severe water scarce conditions for at least one month of the year; 3.3 billion for at least three months; and 1.8 billion for at least half a year. Climate change has also created more uncertainty in water availability, increased risk, and production and economic losses (Wiltshire et al, 2013;Mekonnen and Hoekstra, 2016;Singh et al, 2017;Sishodia et al, 2018;Malek et al, 2018;Lu et al, 2019;Aggarwal et al, 2019). As agriculture is the largest consumer of freshwater, its declining availability has a direct impact on food security, sustainability, and livelihoods for millions of rural households, especially in developing countries like India (Berchoux et al, 2019;Garg et al, 2020;Zarei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%